1998
DOI: 10.1590/s0034-89101998000200006
|View full text |Cite
|
Sign up to set email alerts
|

Factores de riesgo para el desarrollo psicomotor en lactantes nacidos en óptimas condiciones biológicas

Abstract: OBJECTIVO: Evaluar el efecto de factores de riesgo para el desarrollo infantil en niños, de nivel socioeconómico bajo, nacidos en óptimas condiciones biológicas pero expuestos a condiciones sociales adversas. METODOLOGÍA: Lactantes de ambos sexos em número de 788, fueron exhaustivamente estudiados en términos de: alimentación, crecimiento, ambiente físico y psicosocial. Se controlaron prospectivamente hasta los 12 meses de edad, momento en que se evaluó el desarrollo mental (MDI) y motor (PDI) a través de la e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1
34

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 16 publications
2
38
1
34
Order By: Relevance
“…These interactions facilitate mental processes responsible for cognitive development, such as discrimination, perception, and learning. As a result, the absence of stimulating materials can decrease the effectiveness of proximal processes and limit competency development 9,22,30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These interactions facilitate mental processes responsible for cognitive development, such as discrimination, perception, and learning. As a result, the absence of stimulating materials can decrease the effectiveness of proximal processes and limit competency development 9,22,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Poor quality of home environment stimulation can adversely affect children's development, leading to cognitive deficits 22,23 and subsequently to behavioral disorders 37,38 . However, one should bear in mind that the HOME inventory, although widely applied in a variety of cultural backgrounds, may not be perfectly suitable for measuring the quality of the environment of Brazilian children, especially those from low-income families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 In the present study, maternal schooling showed no association with the condition of the NPMD, a fi nding observed in other work. 26 Studies have shown that the level of maternal education involves a situation of vulnerability for children in early childhood, revealing an important association between this variable and development delays. 17,19,25 In fact, the educational level of the parents is a predictive factor of development, since the length of time studying is closely related to cognitive skills that parents use to stimulate their children.…”
Section: Discussionmentioning
confidence: 99%
“…, 3 However, the CNS is not the only factor responsible for motor development, it is also related to the musculoskeletal development and cardiorespiratory fitness, all influenced by stimuli and environmental factors 47 There is evidence that low socioeconomic status8 - 11 and family and school environment of poor quality can negatively influence the development of healthy children,8 , 10 , 12 , 13 while favorable environmental conditions, such as adequate stimuli, higher maternal education and socioeconomic status seem to positively influence children's motor and cognitive development 814 - 16 …”
Section: Introductionmentioning
confidence: 99%